Functional Structural Theory and Economic Empowerment among MSMEs in Rural Areas - Yanti, Lesti Heri; Wijayanti, Ayu; Anggraini, Ayu; Emilda, Syahria; Sari, Rosi Puspita (Jurnal Ilmiah Mandala Education (JIME), 2025)
MSMEs are one of the economic sectors that have a strategic role in the village economy, the role of MSMEs in the economy is also influenced by various factors including village potential, infrastructure, government policies, and synergy between village MSMEs, Therefore, the Makassar Maju College of Economics created a main work program for the Socialization of "The Role of MSMEs for the Bonto Daeng Village Community" the purpose of the MSME Socialization in Bonto Daeng Village is to motivate the community to form MSMEs. The existence of MSMEs in the village can also reduce unemployment by opening up new employment opportunities, From the results of observations made in Bonto Daeng Village, the opportunity to create MSMEs is quite capable when viewed from the aspect of abundant agricultural products from the plant and fruit sectors in the village. Moreover, this village does not yet have MSMEs, so the results of the Socialization of "The Role of MSMEs for the Community of Bonto Daeng Village" were able to motivate people to create MSMEs in the village.